4x+23+10x-1=78+78+x

Simple and best practice solution for 4x+23+10x-1=78+78+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+23+10x-1=78+78+x equation:



4x+23+10x-1=78+78+x
We move all terms to the left:
4x+23+10x-1-(78+78+x)=0
We add all the numbers together, and all the variables
4x+10x-(x+156)+23-1=0
We add all the numbers together, and all the variables
14x-(x+156)+22=0
We get rid of parentheses
14x-x-156+22=0
We add all the numbers together, and all the variables
13x-134=0
We move all terms containing x to the left, all other terms to the right
13x=134
x=134/13
x=10+4/13

See similar equations:

| 5/6x+1=-1.2x+1/4 | | 4x-8=4x+24 | | 3(5x-2)-5=17+x | | 42x+1=8 | | 2x+40=-12 | | -6(2x+4)+1/2(8x+3x)=-20 | | Y^3y+2=0 | | 18x8/2=13 | | 42x+1+85=180 | | 2=|8-y|=30 | | 16x-4=-12+8x | | -1.3+2z=-5/6 | | 56x+1=−12x+14 | | 1/2(x+10)=15=-3 | | -7x+8=-5x+2 | | 16x+19+65=180 | | 3x-19+91=180 | | 6(2m-4)=4(3m-6) | | 2z+9+6z-20+z+11=180 | | (5x-8)(6x+6)=0 | | 4(x-1)-3(x-2)=- | | 5+7x+10x=44 | | 1.63-6.3n=0.26 | | 112=-7(x+2) | | -8+11x+100=180 | | n/3+19=26 | | 4.5(x-0.4)=7.2 | | 180=(x+10)+3x+2x | | 6(x–5)=18 | | 9=3(x−11) | | -4x+2=-54 | | x/7-3/14=1 |

Equations solver categories